Catalytic enantioselective reductive domino alkyl arylation of acrylates via nickel/photoredox catalysis - Pengcheng Qian (Nature Portfolio, 2021)
Enantioenriched α-aryl propionic acids are an important class of nonsteroidal anti-inflammatory medications. Here the authors use a visible-light-promoted photoredox/nickel catalyzed method to form such compunds via a three-component alkyl arylation of acrylates.